Implementation of Problem Based Learning Model to Improve Problem Solving Ability in Static Fluid Material - Dewi Syahbandi; Muhammad; Hasbullah; Zulkarnaini (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve students' problem solving by implementing the Problem Based Learning learning model. The sample used in this study was 30 students of class XI IPA-2. This study used a pre-experimental research design with a one group pre-test and post-test design, problem solving data were collected through essay pre-test and post-test questions. Analysis of problem solving data was tested with statistics, namely the N-Gain test, hypothesis testing using the Paired Sample T.Test. The results of the problem solving data analysis obtained an average pre-test value (67) and post-test (96) with an average N-Gain (0.81) in the high category. The results of hypothesis testing on the Paired sample T-Test obtained a sig value (2-tailed) of 0.000 <0.05, thus the results stated that the hypothesis testing in the study showed that Ha was accepted and Ho was rejected. It can be concluded that the application of the Problem Based Learning learning model can improve problem solving for class XI IPA-2 students at SMA Negeri 1 Peukan Bada on static fluid material.